NETWORKS OF QUALITY IMPROVEMENT - Cevallos A., Juan (2004)
This article deals about the need of better highly-powered tools for quality improvement. A creative combination of Continuous Improvement Philosophy, Systems General Theory and Network General Theory is used, with the purpose of developing a Quality Improvement Network allowing an optimization of systems and processes within organizations.